Abnormal aortic hemodynamics at predilection sites for dissection in patients with Marfan Syndrome: a 4D flow study. (13th July 2021) - Van Andel, MM; Van Ooij, P; Gottwald, L; De Waard, V; Zwinderman, AH; Mulder, BJM; Nederveen, AJ; Groenink, M
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): AMC Foundation Horstingstuit Foundation Introduction: Patients with Marfan syndrome (MFS) may develop aneurysmatic dilatation and dissection of the aorta with a consequence of sudden death at relatively young age. We performed an aortic 4D flow MRI analysis, providing a comprehensive quantification and visualization of abnormal aortic velocity and wall shear stress (WSS) magnitude and direction with recently developed techniques (1, 2). We hypothesize that abnormal hemodynamics are found at predilection sites for aortic dissection in MFS patients. Methods: This prospective study included 56 MFS patients and 25 healthy subjects as controls. Aortic 4D flow MRI was performed on a 3T Philips Ingenia system (Best, Netherlands). The aorta was manually segmented on time-averaged phase contrast MR angiogram images (phase contrast images multiplied by absolute velocity) by thresholding, watershed, and manual voxel in-/exclusion. The segmentations were used to mask the velocities, calculate WSS, and co-registration for quantification of abnormal hemodynamics (3). Abnormally elevated velocity and WSS were defined as higher than the three-dimensional 95% confidence interval as determined in the control group. Abnormally directed velocity and WSS were defined as vector angle differences higher than 120°. The aorta was subdivided in six regions of interest (ROIs) for total multiple linear regression with age, aortic diameter, and blood pressure characteristics. Independent predictors were defined as characteristics that were significant in the total model. Significance was defined as p < 0.05 with Bonferonni correction. The 3D-maps with abnormal hemodynamics were co-registered and added to create 3D-maps that show the incidence of abnormal hemodynamics. Results: Figure 1 shows examples of maps with abnormal velocity and WSS magnitude and direction respectively. Ascending elevated velocity was associated with age, aortic diameter and blood pressure characteristics, whereas elevated WSS was associated with blood pressure characteristics only. No independent predictors were found for abnormally directed hemodynamics. Figure 2 shows the incidence maps for abnormally elevated velocity and abnormally directed WSS in two patients. The maximum incidence for elevated velocity and WSS were 32% and 20%, respectively, and found in the ascending aorta. The maxima for abnormally directed velocity and WSS were 18% and 39%, respectively, and found in the inner proximal descending aorta. Conclusion: Altered aortic geometry and wall properties in MFS patients cause detectable hemodynamic effects in 30% of our cohort at known predilection sites for aortic dissection in MFS patients: the ascending aorta and proximal descending aorta. Independent measures of altered hemodynamics could possibly indicate individual patients at risk for aortic dissection.